Problems in the Agricultural Development of Northern 1950 Year (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
The 1950s were a period of complex socio-economic and demographic changes in the history of the country. Economic life in the villages was mainly concentrated in collective farms, which maintained a difficult situation. The consequences of the Second World War, natural climatic conditions, the dominance of manual labor, and administrative command methods of leadership had a great impact on the origin of such a complex economic situation.